2017
DOI: 10.1007/s10457-017-0132-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial similarities between European agroforestry systems and ecosystem services at the landscape scale

Abstract: Agroforestry systems are known to provide ecosystem services which differ in quantity and quality from conventional agricultural practices and could enhance rural landscapes. In this study we compared ecosystem services provision of agroforestry and non-agroforestry landscapes in case study regions from three European biogeographical regions: Mediterranean (montado and dehesa), Continental (orchards and wooded pasture) and Atlantic agroforestry systems (chestnut soutos and hedgerows systems). Seven ecosystem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 51 publications
(41 reference statements)
2
27
1
Order By: Relevance
“…The study areas were identified as landscapes that most residents identify with and/or depend on for their lifestyles and livelihoods based on knowledge of local members of the research team (Brown et al, 2015b). They represent the major types of multifunctional landscapes in Europe and spread across a large gradient of land-use and biogeographic conditions (Kay et al, 2017) and degrees of rurality ( Supplementary Table A.1). Following the FARO typology of rurality (van Eupen et al, 2012), our study areas cover situations from "deep rural" (e.g.…”
Section: Study Areasmentioning
confidence: 99%
“…The study areas were identified as landscapes that most residents identify with and/or depend on for their lifestyles and livelihoods based on knowledge of local members of the research team (Brown et al, 2015b). They represent the major types of multifunctional landscapes in Europe and spread across a large gradient of land-use and biogeographic conditions (Kay et al, 2017) and degrees of rurality ( Supplementary Table A.1). Following the FARO typology of rurality (van Eupen et al, 2012), our study areas cover situations from "deep rural" (e.g.…”
Section: Study Areasmentioning
confidence: 99%
“…Actually, the decision of managing the land as an agroforestry system is not only related to financial profitability but also to other criteria such as to increase the diversification of products, improve biodiversity, animal health and welfare as described by The decline in pollinators and its possible consequence on pollination service has been a key issue at European scale (Zulian et al 2013;Breeze et al 2014). However, as enough nesting and foraging resource for wild pollinators were available in all case study landscapes (Kay et al 2018b), the cost of potentially reduced pollination services had no impact.…”
Section: Carbon Sequestrationmentioning
confidence: 99%
“…Nevertheless, to date, these studies remain the only ones we know of and thus the generality of this approach, as well as further ecological implications must be explored in more detail. Recent studies, suggest that agroforestry has the potential to sequester C also in Switzerland (Kay et al, 2018). Various combinations of woody plants and crops or grasslands exist.…”
Section: Improvement Of Soc In Swiss Agricultural Systemsmentioning
confidence: 99%